Sosialisasi Etika dan Tanggung Jawab Dalam Bisnis Digital di SMA Dian Andalas Padang - Kiki Sarianti; Yolanda Desti; Ramadhi Ramadhi; Desi Rosalina; Nora Damayanti; Edo Andrefson (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
The development of digital technology provides great opportunities for the younger generation to be involved in the business world, but it also brings challenges related to ethics and social responsibility. This study aims to examine the importance of socialization of ethics and responsibility in digital business among students of Dian Andalas Padang High School. Through socialization activities, students are expected to understand the basic principles of ethics in digital business, such as honesty in transactions, personal data protection, and social responsibility to society and the environment. In addition, this activity also aims to increase students' awareness of developing digital issues, such as online fraud and the spread of negative content. The expected result of this socialization is the formation of student characters who are more responsible, independent, and intelligent in using technology positively. With a better understanding of ethics and responsibility, students are expected to develop a sustainable digital business and make a positive impact. Overall, this socialization is expected to equip students with skills and values that support them in becoming successful and integrity digital business actors in the future.